Switching costs and occupational transition into self-employment - Andrew Henley (Institute for the Study of Labor (IZA), 2009)
Contemporary dynamic theories of self-employment choice focus on occupational switching costs, and the risk associated with entrepreneurial income streams. However little or no previous research has addressed the question of what factors determine the length of time that it takes aspiring entrepreneurs to switch into self-employment. The existence of switching costs suggests that choice may be subject to 'hysteresis' (akin to investment under conditions of irreversibility and uncertainty). This paper presents empirical evidence on the dynamics of entrepreneurial transition drawing on data from Waves 8 to 16 of the British Household Panel Survey. The paper estimates a discrete-time duration model of the time between initial expressions of aspiration to transition into self-employment. The model incorporates measures of local economic volatility to capture uncertainty, as well as a range of demographic and background factors which may be associated with lower switching costs. Econometric results reveal that switching costs are lower for men, older individuals and graduates, as well as for those with prior entrepreneurial experience. Increased volatility in the local housing market is also found to be associated with slower transition, suggesting that information about the housing market may form an important indicator of uncertainty for aspiring entrepreneurs.
urn:nbn:de:101:1-2009021087
Keywords: J23; J24; C23; 330; Self-employment; entrepreneurship; switching costs; occupational choice; Berufswahl; Selbstständige; Unternehmer; Wechselkosten; Schätzung; Großbritannien